The Use of Endemic Pinang Fruit As a Media For Science Learning at Muhammadiyah Primary School Lab School Unimuda Sorong - Wafatolo, Ever; Ihsan, Ihsan; Faizin, Muhammad; Rahayu, Desti (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2025)
This research examines the use of areca nut (Areca catechu) as a medium for learning Natural Sciences (IPA) at SD Muhammadiyah Lab School Unimuda Sorong. This research aims to explore the impact of using areca nut on students' understanding of science concepts, as well as the challenges faced in its implementation. Using a descriptive qualitative approach, data was collected through observation, interviews and documentation. The results of the research show that the use of areca nuts can increase student involvement in learning, introduce science concepts that are easier to understand, and raise awareness of local wisdom and the importance of environmental conservation. However, there are challenges related to the limited understanding of teachers in using this media effectively and the limited educational infrastructure in the area. This research suggests the need for training for teachers and improving educational facilities to optimize the use of nature-based learning media. It is hoped that the use of local wisdom in education can enrich students' learning experiences and strengthen their understanding of natural sciences.